1998
DOI: 10.1074/jbc.273.49.32910
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Promoters and Developmental Modulation of Expression of the Chicken GATA-2 Gene in Hematopoietic Progenitor Cells

Abstract: We have isolated and characterized the chicken GATA-2 (cGATA-2) gene. We show that, as in the case of some other members of the GATA gene family, the gene is expressed from alternative first exons. One of the resulting mRNAs represents only a minor form of the GATA-2 mRNA in the cells and tissues we analyzed; the other is ubiquitously expressed. We have defined the minimal promoter that controls expression of this most abundant mRNA and that is necessary for full activity in hematopoietic progenitor cells. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 48 publications
1
13
0
1
Order By: Relevance
“…We find that by contrast to chicken GATA-6, which is transcribed from a single promoter (9), the mammalian genes both contain two alternative noncoding upstream exons, transcribed from two distinct promoters, as reported previously for some other members of the GATA family (2,10,11,12). By a combination of RNase protection analysis, exon-specific in situ hybridization, and RT-PCR, we have not detected any difference in the spatial expression patterns of the two GATA-6 transcript isoforms.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…We find that by contrast to chicken GATA-6, which is transcribed from a single promoter (9), the mammalian genes both contain two alternative noncoding upstream exons, transcribed from two distinct promoters, as reported previously for some other members of the GATA family (2,10,11,12). By a combination of RNase protection analysis, exon-specific in situ hybridization, and RT-PCR, we have not detected any difference in the spatial expression patterns of the two GATA-6 transcript isoforms.…”
supporting
confidence: 83%
“…Similarly, an upstream promoter within the mouse GATA-2 gene is active only in hematopoietic cells, while a downstream region directs GATA-2 transcription in all cells in which it is expressed (10). Two distinct transcriptional start sites have also been reported for the chicken GATA-2 gene, although the tissue distribution of promoter usage differs from the mouse (9,11). Most notably, the predominant chicken GATA-2 transcript within erythroid cells derives from the proximal promoter, demonstrating evolutionary diversity in the regulation of the GATA-2 gene between avian and mammalian species.…”
Section: The 5ј-utr Does Not Affect the Rate Or Site Of Translationalmentioning
confidence: 98%
“…Interestingly, this intron contains a sequence motif homologous to a regular TATA box (TATAAA) near its 3¢ border. This sequence element could be used as an internal alternative promoter, a situation that has been previously identified in other genes containing an intron within their 5¢ UTR [33]. Alternative splicing and/or use of alternate promoters could contribute to explain previously reported size differences in MGP mRNAs [34,35].…”
Section: Discussionmentioning
confidence: 77%
“…The gene-distal first exon (IS) is specifically expressed in hematopoietic and neural cells, whereas the geneproximal first exon (IG) is transcribed in almost all Gata2-expressing cells (29). Differential utilization of two distinct first exons has also been demonstrated for the human and chicken Gata2 genes (37,44). We also reported that the murine Gata2 gene contains a number of hematopoietic regulatory elements scattered over more than 250 kbp of the locus, since a 250-kbp yeast artificial chromosome transgene was capable of rescuing the hematopoietic lethal deficiency in Gata2 null mutant embryos (66).…”
mentioning
confidence: 84%